2009
DOI: 10.2174/1874325000903010001
|View full text |Cite
|
Sign up to set email alerts
|

High Hydrostatic Pressure for Disinfection of Bone Grafts and Biomaterials: An Experimental Study

Abstract: Abstract:Background: Autoclaving, heat, irradiation or chemical detergents are used to disinfect autografts, allografts and biomaterials for tissue reconstruction. These methods are often associated with deterioration of mechanical, physical, and biological properties of the bone grafts and synthetic implants. High hydrostatic pressure has been proposed as a novel method preserving biomechanical and biological properties of bone, tendon and cartilage. This is the first study to assess the inactivation of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 24 publications
(26 reference statements)
2
33
1
Order By: Relevance
“…High-pressure treatment constitutes a valid alternative to gamma ray irradiation, heat treatment, and chemical inactivation that tend to deteriorate the biomechanical properties of the material. As a matter of fact, high pressure was shown not to alter the biomechanical and immunohistochemical properties of the material while being able to inactivate diverse viruses, bacteria, and fungi (Brouillet et al 2009;Diehl et al 2005;Diehl et al 2006;Gollwitzer et al 2009;Naaletal.2008). Nevertheless, Gollitzer et al showed that bacteria embedded in bones were less prone to high pressure inactivation than bacteria in suspension.…”
Section: Disinfection Of Biomaterialsmentioning
confidence: 99%
“…High-pressure treatment constitutes a valid alternative to gamma ray irradiation, heat treatment, and chemical inactivation that tend to deteriorate the biomechanical properties of the material. As a matter of fact, high pressure was shown not to alter the biomechanical and immunohistochemical properties of the material while being able to inactivate diverse viruses, bacteria, and fungi (Brouillet et al 2009;Diehl et al 2005;Diehl et al 2006;Gollwitzer et al 2009;Naaletal.2008). Nevertheless, Gollitzer et al showed that bacteria embedded in bones were less prone to high pressure inactivation than bacteria in suspension.…”
Section: Disinfection Of Biomaterialsmentioning
confidence: 99%
“…2010) with different objectives: (i) the production of microbiologically safe pharmaceutical preparations (Rigaldie et al. 2003; Van Doorne 2008), (ii) the disinfection of medical devices, biomaterials or natural components (Gollwitzer et al. 2009), (iii) the stabilization of proteins intermediates, in particular the ones found in the aggregation and amyloidogenosis phenomena involved in several neurodegenerative diseases (Torrent et al.…”
Section: The Development Of Hhp Processes For Pharmaceutical and Medimentioning
confidence: 99%
“…Standard decontamination methods (autoclaving, heat, irradiation, chemical detergents) for biomaterials lead to some deterioration of their physical (in particular mechanical) and biological (such as their ability to be invaded by new cells) properties. Some research works were conducted on the use of HHP processes as an alternative to prepare safe biomaterials, consisting either of tumour afflicted bone segments, contaminated biomaterial surfaces or infected bone fragments (Gollwitzer et al. 2009).…”
Section: The Development Of Hhp Processes For Pharmaceutical and Medimentioning
confidence: 99%
See 2 more Smart Citations